FIBRIN GLUE DAN APLIKASINYA - Agi Harliani S (Faculty of Dentistry, Universitas Indonesia, 2015)
Fibrin Tissue Adhesive (FTA), Fibrin Sealant (FS) or Fibrin Glue (FG) are names given to a group of product that lead to the formation of fibrin clot at the site of application. Fibrin Glue represents a new revolution for local haemostatic, which produced by based on the understanding about blood coagulation process. The mechanism of FG mimics the last stage of blood coagulation process. Haemophilia, is a congenital inherited bleeding disorder, characterized by repeated bleeding episodes. The basic pathology is deficiency of factor VIII (hemophilia A) or factor IX (hemophilia B). At bleeding episodes, hemophilia patients need replacement therapy. Hemophilia patients need transfusion of cryoprecipitate, Fresh Frozen Plasma (FFP) or factor concentrate as replacement therapy. Oral surgery, dental extraction, circumcision, and orthopedic operations are the most important indications for fibrin glue in hemophilia care. As haemostatic local, FG minimizes bleeding, reducing the need of transfusion or factor concentrate, reducing the complication of transfusion, hospitalization and cost.